A study on the adequacy of national forestry amend act 1993 on illegal logging and its enforcement in Malaysia / Ahmad Kamal Nazmi Kamarul Zafik …[et al.] - Kamarul Zafik, Ahmad Kamal Nazmi; Abd. Rahman, Yasmin Afifa; Bernard, Cheryl Christy; Raja Yaakob, Raja Zul Adli; Ahmad, Muhammad Zikri; Sidek, Muhammad Rahimi (2010)
This research is carried out in order to investigate the reason behind Illegal Logging in Peninsular Malaysia. Our group would like to pinpoint what is exactly the weaknesses that enable illegal logging to occur in Malaysia so that actions can be taken to rectify the problems. We have to investigate whether the law on illegal logging as stipulated in the National Forestry Act 1993 is lacking or the enforcement of the law by the enforcer itself is ineffective. There are several sections in the National Forestry Act 1993 which are specifically dedicated for illegal logging and its punishment. As for the enforcement on illegal logging, there are several government agencies that have the jurisdiction to take actions on illegal logging, such as the State Forestry Department, Royal Police of Malaysia, Royal Customs of Malaysia and other agencies. After several months of scrutinizing almost hundreds of articles be it online or hard copy, and after conducting an interview with a Forestry Department's Officer of Selangor, we have arrived to several conclusions on illegal logging. We have found that the law relating to illegal logging is indeed adequate to deter criminals; however, we found that the problems are in the enforcement itself. The three main problems are the lack of co-operation between government agencies in fighting illegal logging, lack of monetary provision and manpower for the enforcer and lastly, bribery.